2022
DOI: 10.3390/md20040256
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpse at Siderophores Production by Anabaena flos-aquae UTEX 1444

Abstract: In this study, a strain of Anabaena flos-aquae UTEX 1444 was cultivated in six different concentrations of iron (III). Cultures were extracted with organic solvents and analyzed using our dereplication strategy, based on the combined use of high-resolution tandem mass spectrometry and molecular networking. The analysis showed the presence of the siderophores’ family, named synechobactins, only in the zero iron (III) treatment culture. Seven unknown synechobactin variants were present in the extract, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Combining this information with those coming from our previous study [ 31 ], a new set of cultures was prepared, in which the concentration of Fe 3+ , supplemented as ferric ammonium citrate in FWBG11, has been varied from 0 µM to 5 μM. Taking into account that µM quantities of citrate are necessary to promote synechobactin production ( Figure 3 ), sodium citrate has been supplemented to each of the above cultures in the amount necessary to compensate for the citrate removed with the ferric ammonium salt.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Combining this information with those coming from our previous study [ 31 ], a new set of cultures was prepared, in which the concentration of Fe 3+ , supplemented as ferric ammonium citrate in FWBG11, has been varied from 0 µM to 5 μM. Taking into account that µM quantities of citrate are necessary to promote synechobactin production ( Figure 3 ), sodium citrate has been supplemented to each of the above cultures in the amount necessary to compensate for the citrate removed with the ferric ammonium salt.…”
Section: Resultsmentioning
confidence: 76%
“…We have previously reported that Anabaena flos aquae UTEX 1444 produces a cluster of chemically related siderophores (including schizokinen, rhizobactin 1021, synechobactin, and aerobactin) in a condition of iron limitation [ 31 , 32 ]. Till now, the yield of these siderophores from Anabaena flos aquae has been low [ 31 ]. Schizokinen is one of the most structurally well-defined hydroxamate siderophores and is produced by some Anabaena species in freshwater [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations